Efektivitas Manajemen Berbasis Madrasah Dalam Mengembangkan Kompetensi Guru Di MIN 6 Aceh Timur - Murhaban Murhaban; Andika Aprilianto; Hani Adi Wijono (LP3M IAI Al Urwatul Wutsqo Jombang, 2024)
This research aims to analyze the effectiveness of Madrasah-Based Management (MBM) in developing teacher competency at MIN 6 East Aceh. This research uses a descriptive qualitative approach with a case study method. Data sources were obtained through interviews, observation and documentation. The research results show that implementing MBM in MIN 6 East Aceh has generally gone well despite several obstacles. In the aspect of developing teacher competency, MIN 6 East Aceh has made efforts such as providing opportunities for teachers to improve their educational qualifications, developing educator management through internal Teacher Working Groups (KKG), and providing opportunities to attend seminars. Factors supporting the implementation of MBM in MIN 6 East Aceh include strong leadership of the madrasa head, availability of human resources, adequate facilities and infrastructure, and fairly high community participation. The inhibiting factors in implementing MBM at MIN 6 East Aceh include limited classroom space, lack of networks and community participation, still centralized administration, and limited budget to develop teacher competency. To overcome these obstacles, MIN 6 East Aceh needs to strengthen networks and partnerships with the community, seek to increase the budget to support training and professional development activities for teachers and increase the number of classrooms. Overall, the implementation of MBM at MIN 6 East Aceh has positively impacted the development of teacher competency and improved the quality of education in madrasas.